2022
DOI: 10.1155/2022/7512736
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Characteristics of Diabetes Complicated by Bacterial Liver Abscess and Nondiabetes-Associated Liver Abscess

Abstract: Background. Bacterial liver abscess (BLA) is a secondary infectious disease caused by hepatic parenchymal inflammation and bacterial necrosis. Studies have shown that diabetic patients with BLA have higher rates of related adverse events than patients without diabetes. Aim. To explore the clinical characteristics of BLA complicated with diabetes and nondiabetes-related BLA. Methods. From January 2019 to June 2020, 61 diabetic patients with BLA were included as the study group, and 61 BLA patients without diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In this study, DM remained the prevailing comorbidity in patients with PLAs, accounting for about 37% of cases and exhibiting no significant change in recent years. [26][27][28][29] Coexisting DM increases the risk of portal infection, weakens the liver's immune response, and impairs the body's ability to clear bacteria. 30 The incidence of patients with PLAs was also observed to be elevated in patients with a history of abdominal surgery, particularly hepatobiliary and pancreatic procedures, which is thought to result from changes in the microbiome and intestinal barrier, as well as a compromised immune system.…”
mentioning
confidence: 99%
“…In this study, DM remained the prevailing comorbidity in patients with PLAs, accounting for about 37% of cases and exhibiting no significant change in recent years. [26][27][28][29] Coexisting DM increases the risk of portal infection, weakens the liver's immune response, and impairs the body's ability to clear bacteria. 30 The incidence of patients with PLAs was also observed to be elevated in patients with a history of abdominal surgery, particularly hepatobiliary and pancreatic procedures, which is thought to result from changes in the microbiome and intestinal barrier, as well as a compromised immune system.…”
mentioning
confidence: 99%
“…The risk of bacterial liver abscess in DM is approximately 3.6–11 times higher than in individuals without DM 45 . Rates are highest in individuals from Asian countries.…”
Section: Methodsmentioning
confidence: 98%
“…The risk of bacterial liver abscess in DM is approximately 3.6-11 times higher than in individuals without DM. 45 Rates are highest in individuals from Asian countries. The diagnosis should be considered where there is unexplained right upper abdominal pain, rigors and fever.…”
Section: Liver Abscessmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%